The Discharge Danger Zone: A Systematic Review of Systemic, Communicative, and Inter-Professional Barriers to Safe Hospital-to-Home Transitions - Mir Hasib; Malaika Taseen (Home Health Care Management & Practice, 2026)
Background: The acute hospital-to-home transition is a period of profound clinical vulnerability. While systems track readmission metrics, the communicative and environmental friction points burdening nursing practice remain fragmented in the literature. Current models frequently treat discharge as an idealized administrative task, overlooking the complex realities of the “discharge danger zone” that impede effective patient education. Objective: This systematic review synthesizes international empirical evidence to identify the pervasive communication failures, inter-professional workflow constraints, and cognitive-environmental barriers disrupting the clinical provider-to-home handoff. Methods: Designed as a mixed-methods systematic review (PROSPERO: CRD420261435583) guided by JBI methodology, a search of 6 databases identified 30 peer-reviewed empirical studies published between 2020 and 2026. Methodological quality was appraised using the Mixed Methods Appraisal Tool (MMAT). Data were synthesized using a convergent integrated mixed-methods approach. Results: Four macro-themes mapping transition breakdowns emerged: (1) Cognitive, Psychosocial, and Health Literacy Barriers; (2) Systemic and Workflow Friction Points (e.g., rushed timelines, fragmented coordination); (3) Environmental, Socioeconomic, and Structural Home Barriers; and (4) Communication Quality and Information Processing Breakdowns (e.g., medical jargon, lack of comprehension verification). These intersecting forces routinely sabotage patient education, cultivating a perilous “illusion of comprehension.” Conclusion: The hospital-to-home transition is a complex inter-professional communication event, not merely a medical transaction. To enhance patient safety, nursing leadership must advocate for systemic workflow redesigns that decouple transition education from the rushed point of exit, mandate structured comprehension verification, and implement interventions accommodating patient cognitive load and diverse social environments.